Measurement of the top quark charge in $pp$ collisions at $\sqrt{s} =$ 7 TeV with the ATLAS detector - ATLAS collaboration (2914 authors); Aguilar-Saavedra, Juan Antonio; Amor Dos Santos, Susana Patricia; Anjos, Nuno; Cantrill, Robert; Carvalho, João; Castro, Nuno Filipe; Conde Muiño, Patricia; Da Cunha Sargedas De Sousa, Mario Jose; Do Valle Wemans, André; Fiolhais, Miguel; Galhardo, Bruno; et al. (My University, 2013)
A measurement of the top quark electric charge is carried out in the ATLAS experiment at the Large Hadron Collider using 2.05 fb-1 of data at a centre-of-mass energy of 7 TeV. In units of the elementary electric charge, the top quark charge is determined to be 0.64 +- 0.02 (stat.) +- 0.08 (syst.) from the charges of the top quark decay products in single lepton ttbar candidate events. This excludes models that propose a heavy quark of electric charge --4/3, instead of the Standard Model top quark, with a significance of more than 8 sigma.